Dynamic uses of memory in visual search over time and space - Humphreys, G; Braithwaite, J; Olivers, C; Watson, D (Springer Tokyo, 2005)
We review evidence on the use of one type of memory in visual search over time. Visual search benefits when observers are given a preview of distractors that remain throughout a subsequent search display. Studies examining negative carry-over effects and visual probe detection suggest that the 'preview benefit' is based at least in part on the inhibition of old groups of stimuli. However, the presence of luminance onsets defining the new search display are not necessary to produce the benefit, since, under appropriate conditions, a benefit can occur when the new stimuli do not have unique luminance onsets. Studies using functional brain imaging suggest that the inhibition of old groups of stimuli is modulated by the superior parietal lobe, whereas the detection of salient new targets is associated with activation in the temporo-parietal junction. Dynamic inhibition of memory representations of old stimuli provides a means of prioritizing attention to new events. © 2005 Springer-Verlag Tokyo.